Ileal Conduit Versus Orthotopic Neobladder Urinary Diversion in Robot-assisted Radical Cystectomy: Results from a Multi-institutional Series - Stefano Tappero; Paolo Dell'Oglio; Maria Angela Cerruto; Rafael Sanchez Salas; Oscar Buisan Rueda; Giuseppe Simone; Kees Hendricksen; Francesco Soria; Paolo Umari; Alessandro Antonelli; Alberto Briganti; Francesco Montorsi; et al. (European Urology Open Science, 2023)
Background: Head-to-head comparisons between ileal conduit (IC) and orthotopic neobladder (ONB) in terms of peri- and postoperative outcomes and complications, in the specific setting of robot-assisted radical cystectomy (RARC), are not available. Objective: To address the impact of the type of urinary diversion (UD, IC vs ONB) on RARC morbidity, as well as operative time (OT), length of stay (LOS), and readmissions. Design, setting, and participants: Urothelial bladder cancer patients treated with RARC at nine high-volume European institutions between 2008 and 2020 were identified. Intervention: RARC with either IC or ONB. Outcome measurements and statistical analysis: Intra- and postoperative complications were collected and reported according to the Intraoperative Complications Assessment and Reporting with Universal Standards recommendations and European Association of Urology guidelines, respectively. Multivariable logistic regression models tested the impact of UD on outcomes, after adjustment for clustering at single hospital level. Results and limitations: Overall, 555 nonmetastatic RARC patients were identified. In 280 (51%) and 275 (49%) patients, an IC and an ONB were performed, respectively. Eighteen intraoperative complications were recorded. The rates of intraoperative complications were 4% in IC patients and 3% in ONB patients (p = 0.4). The median LOS and readmission rates were 10 versus 12 d (p < 0.001) and 20% versus 21% (p = 0.8) in IC versus ONB patients, respectively. At a multivariable logistic regression analyses, the type of UD (IC vs ONB) reached the independent predictor status for prolonged OT (odds ratio [OR]: 0.61, p = 0.03) and prolonged LOS (OR: 0.34, p < 0.001), but not for readmission (OR: 0.92, p = 0.7). Overall, 513 postoperative complications were experienced by 324 patients (58%). At least one postoperative complication was experienced by 160 (57%) IC patients versus 164 (60%) ONB patients (p = 0.6). The type of UD reached the status of an independent predictor of UD-related complications (OR: 0.64, p = 0.03). Conclusions: Compared with RARC with ONB, RARC with IC is less prone to UD-related postoperative complications, prolonged OT, and prolonged LOS. Patient summary: To date, the impact of the type of urinary diversion, namely, ileal conduit versus orthotopic neobladder, on peri- and postoperative outcomes of robot-assisted radical cystectomy is unknown. Based on a rigorous data accrual, which relied on established complication reporting systems (Intraoperative Complications Assessment and Reporting with Universal Standards and European Association of Urology recommended systems), we reported intra- and postoperative complications according to urinary diversion type. Moreover, we found that ileal conduit was associated with lower operative time and length of stay, and yielded a protective effect in terms of urinary diversion–related complications.